Rainforest trees respond to drought by modifying their hydraulic architecture. Issue 24 (11th December 2018) - Tng, David Y. P.; Apgaua, Deborah M. G.; Ishida, Yoko F.; Mencuccini, Maurizio; Lloyd, Jon; Laurance, William F.; Laurance, Susan G. W.
Abstract: Increased drought is forecasted for tropical regions, with severe implications for the health and function of forest ecosystems. How mature forest trees will respond to water deficit is poorly known. We investigated wood anatomy and leaf traits in lowland tropical forest trees after 24 months of experimental rainfall exclusion. Sampling sun‐exposed young canopy branches from target species, we found species‐specific systematic variation in hydraulic‐related wood anatomy and leaf traits in response to drought stress. Relative to controls, drought‐affected individuals of different tree species variously exhibited trait measures consistent with increasing hydraulic safety. These included narrower or less vessels, reduced vessel groupings, lower theoretical water conductivities, less water storage tissue and more abundant fiber in their wood, and more occluded vessels. Drought‐affected individuals also had thinner leaves, and more negative pre‐dawn or mid‐day leaf water potentials. Future studies examining both wood and leaf hydraulic traits should improve the representation of plant hydraulics within terrestrial ecosystem and biosphere models, and help fine‐tune predictions of how future climate changes will affect tropical forests globally. Abstract : Understanding how tropical rainforest trees will respond to climate change is important given worrisome projection drought events in tropical regions. We found that mature tropical trees can modify their water transport mechanisms when exposed to drought, at least in the short term. These results allow us to highlight complexities for understanding plant responses to climate change.